Biology learning tasks variation during COVID-19 pandemic and its effect on students’ self-efficacy - Dewi Utami Tuzzahra; Adi Rahmat; Yanti Hamdiyati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
Changes in the learning process during the COVID-19 pandemic require quick adaptation from teachers and students to immediately achieve learning goals. However, it remains ineffective, resulting in a threat of learning loss. This condition can be overcome if students have confidence in their abilities or self-efficacy. It is important to do an analysis related to biology learning tasks taught by the teachers and students’ self-efficacy. This study aims to analyze biology learning tasks variation during the COVID-19 pandemic and its effect on students’ self-efficacy. This study used descriptive design with cross-sectional survey method. Samples were taken using the convenience sampling technique from five public schools. 446 students out of 465 total students and seven biology teachers participated in this study as respondents. The instruments used in this study were rubrics for quantifying learning tasks and self-efficacy questionnaires given to students after Biology Learning. The results show that all learning modes in Biology Learning during the COVID-19 pandemic have learning tasks that were more dominant in the low-level cognitive process. The dominant learning tasks include retrieval and comprehension, while learning tasks with a higher level of cognitive processing such as analysis, knowledge utilization, and metacognitive only cover a small part of the whole Biology learning process. There were no learning tasks that reached the highest level of cognitive process (self-system). The result of self-efficacy in all learning modes was high, but it was higher in learning modes that used hybrid learning. Biology learning tasks given by the teachers during the COVID-19 pandemic have an effect on students’ self-efficacy.